POSSIBILITIES OF MORE PERSPECTIVE DEVELOPMENT OF THE HUNTING GROUND "KARAĐORĐEVO" AS PART OF RURAL TOURISM OFFER - Manojlovic, Radoslava; Stamenkovic, Igor; Matejevic, Milosava; Ristic, Zoran; Gajic, Tamara (Economics of Agriculture, 2021)
In the territory of Vojvodina, there are numerous hunting grounds that are in the ranks of the most elite hunting grounds in Serbia and the wider region. One of them is the hunting ground "Karađorđevo". The aim of the study was to determine what are the characteristics of the hunting destination and elements of the hunting tourism product that are important to hunting tourist when going on a journey. The goal was to determine how much the hunting tourists are satisfied with their hunting experience in this hunting area. The results showed that the most important was the quality of the hunting organization, and the least significant were additional contents of tourist animation. The natural resources of the area are the elements that hunters were most satisfied with. Respondents are less satisfied with the quality of accommodation and are least satisfied with the complementary tourist offer.